Pediatric Meniere's disease. (February 2018) - Wang, Chi; Wu, Chien-Hao; Cheng, Po-Wen; Young, Yi-Ho
Abstract: Objective: This study adopted an inner ear test battery comprising audiometry, and ocular vestibular evoked myogenic potential (oVEMP), cervical VEMP (cVEMP), and caloric tests to investigate the sequence of inner ear deficits in pediatric Meniere's disease (MD). Methods: From 2005 to 2016, a total of 24 MD children aged <15 years old underwent otoscopy, CT scan, blood test, and an inner ear test battery. Nine subjects were males and 15 were females, with mean age of 12 years. Right ear was affected in 3 patients, left ear in 5 patients, and both ears in 16 patients (67%). Eight (33%) of the 24 MD children had positive family history. Results: Inner ear deficits in MD children ran from abnormal hearing (25%) to abnormal cVEMP (20%), oVEMP (13%), and caloric (12%) tests, exhibiting a significantly declining sequence from the cochlea, to the saccule, utricle and semicircular canals. Analysis between the laterality and family history revealed a significantly positive correlation. Conclusion: Pediatric MD is rare, accounting for 2.3% prevalence in MD patients. The inner ear deficits in pediatric MD showed a significantly declining sequence from the cochlea, to the saccule, utricle and semicircular canals, mimicking the sequence in adult MD. One-third MD children had positive family history, which may explain the high rate of bilateral affliction and symmetrical hearing levels on both ears.